The Number of Groups in an Aggregated Approach in Taxonomy with the Use of Stability Measures and Classical Indices – A Comparative Analysis - Rozmus, Dorota (Acta Universitatis Lodziensis. Folia Oeconomica, 2022)
Recently, the two concepts that have been often discussed in the literature on taxonomy are the cluster ensemble and stability. An interesting proposal regarding the combination of these two concepts was presented by Șenbabaoğlu, Michailidis, and Li, who proposed as a measure of stability a proportion of ambiguously clustered pairs (PAC) for selecting the optimal number of groups in the cluster ensemble. This proposal appeared in the field of genetic research, but as the authors themselves write, the method can be successfully used also in other research areas. The aim of this paper is to compare the results of indicating the number of clusters (k parameter) using the aggregated approach in taxonomy and the above-mentioned measure of stability and classical indices (e.g. Caliński–Harabasz, Dunn, Davies–Bouldin).